Chaplin's music hall : the Chaplins and their circle in the Limelight - Anthony, Barry (I.B. Tauris, 2012)
Charlie Chaplin grew up in and around the music hall. His parents, aunt, and their friends all earned their precarious livings on the stage and Chaplin himself started his career as a member of the Eight Lancashire Lads dance troupe. His experiences of the culture of the music hall were a significant influence, shaping his style of acting and the films he made. Chaplin?s family and the circle of fellow performers whose life stories are told in this book were appearing at a time when music hall was in a state of transition, changing from an entertainment still reminiscent of its tavern-based origins to a complex, highly-financed industry seeking legitimacy with a far wider public. As venues grew larger, performers struggled to make connections with an increasingly remote audience.